Noisy Soundscapes and Women's Institutions in Early Modern Florence - Rombough, Julia (The sixteenth century journal, 2019)
This study examines sonic legislation that was increasingly enacted in and around women's institutions (convents, charity homes, and reform houses) in sixteenth-and seventeenth-century Florence. Monitoring the sounds cloistered women made and heard was considered key to reform, the maintenance of social status, and the advancement of bodily/spiritual purity. Efforts to regulate urban sounds were rooted in the belief that sound was a physical force that acted on the body and soul with direct health implications. Sound, silence, and noise were formative agents. Yet sonic regulation was difficult to apply in any absolute sense, as Florentines on both sides of the cloister crafted dynamic urban soundscapes composed of multiple registers. Examining the links between sound, gender, health, and space, this paper reveals how preoccupations with noise and silence had profound implications in the early modern city.